2003
DOI: 10.1177/147323000303100301
|View full text |Cite
|
Sign up to set email alerts
|

Oral Telithromycin 800 mg Once Daily for 5 Days versus Cefuroxime Axetil 500 mg Twice Daily for 10 Days in Adults with Acute Exacerbations of Chronic Bronchitis

Abstract: The efficacy and safety of a 5-day regimen of 800 mg telithromycin once daily was compared with a standard 10-day regimen of 500 mg cefuroxime axetil twice daily in a multicentre, randomized, double-blind, parallel-group trial involving 376 patients with acute exacerbations of chronic bronchitis (AECB). In clinically evaluable patients (n = 282), post-therapy clinical cure rates were 86.4% with telithromycin and 83.1% with cefuroxime axetil. In bacteriologically evaluable patients (n = 53), eradication or pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 27 publications
1
17
0
2
Order By: Relevance
“…The overall telithromycin clinical cure rate in the clinically evaluable per protocol population from these studies was 86% compared with 85.8% for comparator agents. In addition, Zervos et al 64 found that clinical cure rates for a telithromycin 5-day regimen were comparable with those obtained with a 10-day regimen of cefuroxime axetil, even among subjects with poor prognostic indicators. For example, in subjects aged 65 years or older, cure rates with telithromycin and cefuroxime axetil were 89.5% (34/38) and 76.6% (36/47), respectively.…”
Section: Capmentioning
confidence: 85%
See 2 more Smart Citations
“…The overall telithromycin clinical cure rate in the clinically evaluable per protocol population from these studies was 86% compared with 85.8% for comparator agents. In addition, Zervos et al 64 found that clinical cure rates for a telithromycin 5-day regimen were comparable with those obtained with a 10-day regimen of cefuroxime axetil, even among subjects with poor prognostic indicators. For example, in subjects aged 65 years or older, cure rates with telithromycin and cefuroxime axetil were 89.5% (34/38) and 76.6% (36/47), respectively.…”
Section: Capmentioning
confidence: 85%
“…Treatment with short-course (5 days) telithromycin was as efficacious as commonly used antibiotics for a standard duration of 7 to 10 days in 3 phase III randomized, double-blind, multicenter clinical trials in subjects with AECB (Table III). [64][65][66] Adult outpatients were included in the studies if they had a history of chronic bronchitis, chronic obstructive pulmonary disease, and/or symptoms, including increased cough, dyspnea, or both and excessive sputum production or purulence. The overall telithromycin clinical cure rate in the clinically evaluable per protocol population from these studies was 86% compared with 85.8% for comparator agents.…”
Section: Capmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7,10,16,17,20 However, others found cases in which transaminases exceeded three times the upper limit of normal. 6,7,10,18,19,21 A Phase III trial investigating the pharmacokinetics and safety of telithromycin in patients with renal impairment also revealed an increase in liver function test values in three patients. 26 There are some other points worth mentioning about the Phase III comparative efficacy and safety trials conducted with telithromycin.…”
Section: Discussionmentioning
confidence: 95%
“…Telithromycin has been associated with increases in hepatic transaminases in numerous Phase III clinical trials. [6][7][8][9][10][16][17][18][19][20][21] The adverse events related to hepatotoxicity reported in these trials are summarized in Table 1. Some of these trials also found changes in other laboratory test values, including ALP, g-glutamyltransferase, and lactate dehydrogenase, that can also be characteristic of hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%